Prognostic value of inflammatory markers NLR, PLR, and LMR in gastric cancer patients treated with immune checkpoint inhibitors: a meta-analysis and systematic review - Tan, Shufa; Zheng, Qin; Zhang, Wei; Zhou, Mi; Xia, Chunyan; Feng, Wenzhe (Frontiers in Immunology, 2024)
Background Immune checkpoint inhibitors (ICIs) represent a groundbreaking approach to cancer therapy. Inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) have emerged as potential indicators strongly associated with tumor prognosis, albeit their prognostic significance remains contentious. The predictive value of NLR, PLR, LMR in patients with gastric cancer (GC) treated with ICIs has not been fully explored; therefore, we conducted a meta-analysis to examine the potential of inflammatory markers NLR, PLR, and LMR as survival predictors in this population. Methods A comprehensive search was conducted across PubMed, Embase, Web of Science, and Cochrane databases, with the search cut-off date set as March 2024. Hazard ratios (HR) and their corresponding 95% confidence intervals (CI) were calculated to assess the prognostic significance of NLR, PLR, and LMR for both progression-free survival (PFS) and overall survival (OS). Results Fifteen cohort studies involving 1336 gastric cancer patients were finally included in this meta-analysis. The results of the meta-analysis showed that high levels of NLR were associated with poorer OS and PFS in GC patients receiving ICIs, with combined HRs of OS [HR=2.01,95%CI(1.72,2.34),P<0.01], and PFS PFS[HR=1.59,95%CI(1.37,1.86),P＜0.01], respectively; high levels of PLR were associated with poorer OS and PFS, and the combined HR was OS [HR=1.57,95%CI(1.25,1.96),P<0.01], PFS [HR=1.52,95%CI(1.20,1.94),P<0.01] , respectively; and there was an association between elevated LMR and prolonged OS and PFS, and the combined HR was OS [HR=0.62,95%CI(0.47,0.81),P＜0.01], and PFS [HR=0.69,95%CI(0.50,0.95),P＜0.01]. Conclusion In gastric cancer (GC) patients treated with immune checkpoint inhibitors (ICIs), elevated neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were associated with poorer overall survival (OS) and progression-free survival (PFS), while high lymphocyte-to-monocyte ratio (LMR) was linked to improved OS and PFS. Subgroup analyses suggested that NLR might be particularly pertinent to the prognosis of GC patients. In conclusion, the inflammatory markers NLR, PLR, and LMR serve as effective biomarkers for prognostic assessment in GC patients, offering valuable insights for therapeutic decision-making in the realm of GC immunotherapy. Prospective studies of high quality are eagerly awaited to validate these findings in the future.